Hesitancy Of Liz Reflected In Ryan Murphy's Eat Pray Love Movie (2010): A Psychoanalytic Approach. - Safitri, Riana Eko; , Drs. Abdillah Nugroho, M.Hum; , Titis Setyabudi, S.S, M.Hum (2013)
The problem of this study is the hesitancy of Liz reflected in Eat Pray Love movie. The objective of this study is to analyze the structure elements of Eat Pray Love Movie and to analyze the movie based on the psychoanalytic approach. The type of this research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is Video or DVD of Eat Pray Love movie. This movie directed by Ryan Murphy and released in 2010. While the secondary data sources are author's biography, internet related to the study, journals, the notes which are taken by the writer when watching the movie. Both data are collected by conducting library research and analyzed by descriptive analysis. Based on the analysis, the researcher shows some conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, setting, plot, point of view, theme, mise-en-scene, cinematography, sound, casting and editing are supporting each other to give a great quality movie. Second, based on the psychoanalytic analysis, the study shows that the problem faced by the major character is her own psychology condition to bring out her confidence and kill her hesitancy. This movie also shows her extreme desire to take long journey and her experience in many country.